(untitled) (Journal of the College of Basic Education, 2025)
The research objective is to identify the obstacles that limit the integration of artificial intelligence in university education, the researcher used the analytical descriptive method to suit the conditions of her research, the research population consisted of all faculty members in the Department of Mathematics in governmental colleges of Education in Baghdad, there are (162) teachers for the academic year (2025-2024). The research sample consisted of (60) teachers the researcher randomly selected an (actual sample) from the Math Department ,as for the exploratory sample they numbered (25) Teachers from the Math Department, the researcher prepared a questionnaire consisting of (24) paragraphs divided into two axes, The research found some of the obstacles that received a high score including, (lack of awareness affects the quality of education, ai apps become addictive ,anxiety about the accuracy of answers to math problems, artificial intelligence limits creative thinking for math students, the educational experiencev provided by a university prof ensures a deeper understanding of math than artificial intelligence , The researcher made some recommendations including (utilizing experts and specialists in the field of artificial intelligence in universities for the purpose of holding training seminars and workshops, , encouraging university professors to use Modern teaching methods including artificial intelligence, encouraging researchers to advance develop knowledge about artificial intelligence, this study can contribute to proposing solutions to overcome the obstacles that limit the utilization of artificial intelligence in teaching Math in university education .